The Impact of Independent Reading Intervention on Improving Students’ Reading Fluency - Ojeh, Anthonia (LANGUAGE ART, 2022)
Children who love to read have been found to read better, having better vocabulary and text comprehension skills. This study investigated the impact of independent reading in improving students’ reading fluency in a multi-grade reading clinic in a semi-urban community private school in Jos, Plateau State, Nigeria. The research was guided by two research questions: Is traditional classroom phonics instruction enough to develop students’ reading fluency; and can routine independent reading time improve students’ reading fluency? In the study setting, several children were found to read below grade level despite regular synthetic phonics instruction. Thirty-nine students between the ages of 5 and 10 were drawn from a total of 96 students through convenience sampling to take part in the one-sample pre-and post-test study. An initial baseline fluency test eliminated 53.90% of the participants who were reading at an independent level, and the remaining 46.20% were enrolled for the intervention. At the end of the 10-week treatment period, the results showed that about 75% of the participants could read at an independent level while the remaining 25% read at an instructional level. These scores were analyzed using a paired samples t-test to compare reading fluency pre-test and post-test scores. There was a significant difference in the pre-test scores (Mean =90.87), Standard Deviation =4.593 and post-test Mean= 95.55], Standard Deviation=2.139, and p-value = <0.002. This confirms that the impact of IR (Independent Reading) in improving students’ reading fluency was significant. The volume of reading is important for the development of reading competency as it provides students with important practice that helps them gain background knowledge, improve fluency and comprehension, raise motivation, increase reading achievement, and widen vocabulary.